Rancang Bangun Sistem Informasi Penjadwalan Pengiriman Barang pada CV Lestari Mandiri - Wulandari, Kuntari Dwi; Taufiq, Rohmat; Priyanggodo, Dyas Yudi; Daniarti, Yeni (Program Studi Teknik Informatika Universitas Pamulang, 2024)
The Goods Delivery Scheduling System at CV Lestari Mandiri was still carried out conventionally, so the presentation of information regarding goods delivery was still less effective. This research aimed to design and build an information system for scheduling goods deliveries at CV Lestari Mandiri. This information system was expected to increase the efficiency and effectiveness of the goods delivery process by minimizing scheduling errors. The method used in this research was the prototyping method which involves several stages, namely data collection, needs analysis, system design, implementation and testing. Data collection was carried out through direct observation and interviews with parties involved in the goods delivery process at CV Lestari Mandiri. The result of this research was a web-based information system that could be used to manage goods delivery scheduling, including features for entering delivery data, managing schedules, and generating reports. This system was built using the PHP programming language and MySQL Database, and implemented using the XAMPP platform. System testing was carried out using the black box testing method which showed that this system had met user needs and was running as expected.